حماية البيئة من التلوث بالنفايات في الجزائر - بن ڨانه ياسر; موفق عيسى (جامعة الوادي University of El Oued, 2025)
إن المعاناة التي تعيشها الدول جراء التهديدات البيئية، والتي دفعت إلى الدعوة إلى ضرورة حماية البيئة، أصبحت تُشكل تحديًا للقانون بشكل عام وعلى جميع المستويات. فالوسائل القانونية هي الأنسب لحل المشكلات والتعقيدات القائمة. وعلى هذا الأساس، أنشأ المشرع الجزائري وزارةً للبيئة ومجموعةً من الهيئات والمراصد، وأعدّ نصوصًا تنظيمية وتشريعية وإجراءات وقائية ورادعة، وذلك كله بهدف حماية البيئة. إلا أن هذا، مقارنةً بما حققته الدول المتقدمة، يبقى غير كافٍ لضبط وتنظيم السلوكيات والانتهاكات البيئية. The suffering that countries are experiencing due to environmental threats, which has led to the call for the necessity of protecting the environment, has become a challenge to the law in general and at all levels. Legal means are the most appropriate for solving existing problems and complications. On this basis, the Algerian legislator has established a Ministry of the Environment and a group of bodies and observatories, and prepared regulatory and legislative texts and preventive and deterrent measures, all for the purpose of protecting the environment. However, this, in comparison to what developed countries have achieved, remains insufficient to control and regulate behavior and violations against the environment.
قانون إداري
Keywords: حماية، البيئة ، التلوث، النفايات، الجزائر; Protection; Environment; Pollution; Waste; Algeria